Observation of In-Situ Formed Electrolyte from TiH2 by SEM and Windowless EDS - Atsushi INOISHI; Yixin CHEN; Ryoga KONISHI; Hidemasa TSUNEISHI; Takayuki TSUBOTA; Hikari SAKAEBE (Electrochemistry)
This study focuses on the development of in-situ formed solid electrolyte anodes, specifically investigating TiH2 as a promising candidate due to its high theoretical capacity, electronic conductivity, and low operating potential. Using SEM equipped with windowless Energy Dispersive X-ray Spectroscopy (EDS), the lithiation process and distribution of Ti and LiH were analyzed. Two cells (Cell A and Cell B) with differing lithiation capacities (980 mAh g−1 and 623 mAh g−1, respectively) were compared. Results revealed that the reaction in Cell B progressed uniformly throughout the electrode, while in Cell A, lithiation advanced further, forming a thicker LiH layer (0.5 µm) and fragmenting TiH2 particles. Unlike MgH2, which exhibited planar reaction progression, TiH2 undergoes lithiation uniformly along the thickness direction of the electrode layer.